Characterization of the Oral and Esophageal Microbiota in Esophageal Precancerous Lesions and Squamous Cell Carcinoma - Li, Zhengqi; Dou, Lizhou; Zhang, Yueming; He, Shun; Zhao, Deli; Hao, Changqing; Song, Guohui; Zhang, Wei; Liu, Yong; Wang, Guiqi (Frontiers in Cellular and Infection Microbiology, 2021)
Important evidence indicates that the microbiota plays a key role in esophageal squamous cell carcinoma (ESCC). Here, paired saliva and brush specimens were obtained from 276 participants undergoing upper gastrointestinal endoscopic examination before or during screening for upper gastrointestinal (UGI) cancer. The esophageal microbiota was investigated by 16S rRNA gene profiling and next-generation sequencing. We observed that as the disease progressed, the α diversity in the saliva and cell brush samples decreased. Linear discriminant analysis effect size (LEfSe) results showed that in both the saliva and cell brush specimens, Granulicatella, Rothia, Streptococcus, Gemella, Leptotrichia and Schaalia were common biomarkers in patients with low-grade dysplasia, Lactobacillus was a common biomarker in patients with high-grade dysplasia, and Bosea, Solobacterium, Gemella, and Peptostreptococcus were common biomarkers in patients with esophageal cancer. The top 3 genera in the saliva and cell brush specimens had areas under the curve (AUCs) of 87.16 and 89.13%, respectively, to distinguish ESCC patients from normal people. The PICRUSt2 results identified in brush samples that patients with ESCC had decreased nitrate reductase functions. Our results suggest that future studies can focus on the function of the characteristic bacteria in ESCC.